The secret fire /3 - Ringwald, Whitaker (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2016)
Epimetheus wants to control the magical urns that used to belong to Pandora's daughter, and Jax, Ethan, and Tyler's only chance to fight him is a secret weapon--and to realize their family ties are stronger than any magic.